Strategi Pemberdayaan Berdasarkan Undang-Undang Rumah Susun: Studi Komparasi di Rusunawa Harapan Jaya dan Sungai Beliung - Yudith Evametha Vitranilla; Muhammad Fadhly Akbar; Weny Ramadhania; Piramitha Angelina; Sandy Kurnia Christmas (Universitas Muhammadiyah Ponorogo, 2026)
The study examines empowerment strategies implemented at the Harapan Jaya and Sungai Beliung public housing estates and evaluates their effectiveness. This empirical legal study applies the theory of legal effectiveness as an analytical framework. Data were collected through interviews and observations, validated using extended observation and triangulation techniques, and analysed thematically. The findings reveal significant differences in empowerment practices between the two housing estates. At Harapan Jaya, empowerment strategies do not reflect the community-based empowerment model mandated by Article 96 of the Public Housing Act, which emphasises resident participation in public housing management. Residents and managers tend to remain passive and depend on external parties to initiate activities. In contrast, residents and managers at Sungai Beliung actively organise and participate in community-led empowerment programmes. Based on Article 3 of the Public Housing Act, empowerment activities in both estates have not significantly improved residents’ economic conditions. However, Sungai Beliung demonstrates stronger socio-cultural resilience due to regular activities organised through the Renabekati Reading Garden. The study also shows that, although the legal framework for public housing empowerment is theoretically adequate, its implementation varies considerably. Cultural factors, particularly the challenge of managing a heterogeneous community, have not been effectively addressed at Harapan Jaya, resulting in weaker community participation compared to Sungai Beliung.